Analisis Penggunaan Lambung Katamaran Pada Kapal Pengangkut Rumput Laut Di Perairan Buton Tengah - Mubarak, Azhar Aras (Jurnal Teknologi Terpadu, 2025)
Every year seaweed production increases, but the existing transportation facilities are not sufficient. The ships used by seaweed farmers at the research location are still relatively small and not equipped with a more efficient propulsion system. In fact, some farmers still use carts to transport seaweed when the seawater recedes so that the transportation process is ineffective. Fishermen in coastal areas still use very simple technology. Most of the ships used are small in size so that they are less efficient and have limited carrying capacity. Along with the increase in seaweed production every year, more modern transportation facilities are needed so that the work of farmer groups becomes more efficient and provides greater economic value. This study aims to answer these problems by designing ships and analyzing the hydrostatic characteristics of catamaran-type seaweed transport ships. The methods applied include collecting initial data through field observations and direct interviews with fishermen. Furthermore, the ship design was made using AutoCAD software while the calculation of ship strength, stability and hydrostatic conditions of the ship was carried out using Maxsurf software. The project results show that the ship has dimensions of 10 meters long, 3.6 meters wide, 0.337 meters draft, and 7.3 tons displacement. This ship requires 20.65 HP of engine power to reach a speed of 5 knots. Its load capacity is 3,000 kg per day with 60 seaweed ropes. The harvest location is within a radius of 500 meters, so the travel time for one trip is 7 minutes.